Developing Standards of Career Services for Secondary Schools in Malaysia - Ismail, Noraini (2009)
This research was conducted to survey the status and needs of the career services in secondary schools and to build and produce a career services standardization for secondary schools in Malaysia. The method used is generic or basic qualitative research. Triangulation data is obtained by sources from the practitioners’ respondent, standard documents and response of specialist panel. Every data has been analyzed by process of constant comparative. The inspection of data is appertaining to the forming of kategory and themes. The practitioner respondent data are obtained through a focused group discussion. A number of 22 counselors chosen by the purposive sampling and have participated in three focus group discussion where the researcher acted as the moderator. It resulted in having a variation and differences in the way the career services are conducted by the counselors. This is reported happened due a lack of clear guidelines, no specific schedule, lack of competency, lack of information, time limit, work load, lack of support, no source for getting information, no self-improvement course and lack of amenities. Based on these data, this research has identified the needs to have standardization for career services in Malaysian secondary school as well as the career services standard suggested by school counselllors. The document data are obtained from four analyzed documents. From the content of the document, an early draft for the standardization suggestion has been created and evaluated by three of experts. The experts were asked to criticize the early draft, insert additional criteria and give suggestion for improvement. The expert data are obtained from three experts who have been chosen to use the purposive sampling technique. These data were obtained from the critics that have been made by each expert on the early draft and through individual interview with each expert. The interview data are analyzed to identify the suggestion for career service standardization from the point of view of the career experts. There are three types of data obtained (the practitioner data, the document data and the expert data). There data have been analyzed according to the various components and elements discovered. The result shows the standard of career services in Malaysian secondry school. Standard of career services results reveal three parts: Part 1 – General Standard In Services involves components of facilities/material/equipment, qualification/skill of school counsellor including ethics and professionalism. Part 2 - Standard Of Eficiency In The Area Of Services Involving testing and eavaluation, career programme, information/sources/dissemination, career counselling and placement. Part 3 - Standard Of Capability Of Practitioner consists of management and administration, network, technology, consultancy, research, diversity and equality, evaluation programme. The finding of the research has implication on the changing of the career programme policy in secondary schools, raising the base academic and professsional training for the career practitioner as well as the support and cooperation of all parties to build up a career counselling programme in the secondary school. It recoordinates changes in the work technique of the school counsellor to raise up human capital who have directions in future.